Racism in football - Kassimeris, C.; Lawrence, S.; Pipini, M. (Soccer & Society, 2022)
Racism in football is a long-standing phenomenon that has changed shape and form over time. From individual fans either throwing bananas or making monkey-like sounds to organized neo-Nazi fans celebrating on the terraces, the superiority of all things white, non-white football players has long suffered abuse in football. Overlooked by football`s governing bodies for several decades, racism in football was only highlighted in the early 1990s, when the first anti-racism organizations devoted to tackling racist abuse in sport came to life. Thirty years later, the criminal offence that is racism in football not only is still present, but it has also invaded yet another domain of social life-the digital world. The present article, first, addresses notions pertaining to racism in football, then, considers the criminological aspects of digital racisms and, finally, discusses the impact of digital racisms on football studies.